Pink organising: Notes on communication, self-organisation, noise and radical social movements. (September 2019) - Swann, Thomas; Ghelfi, Andrea
This article explores the presence of noise in processes of communication and organisation in social movements. While the concept of noise has always had a role in discussions of communication, it is in light of the influence and use of social media that it comes to the fore as crucial in terms of how we understand communication. Rather than being a factor that interferes with effective communication, we will argue that noise is in fact inseparable from the experience of receiving information and organising through social media. Furthermore, the emergence of different 'nuances' of noise tells us something about different dynamics of self-organisation via social media. This article analyses the online forms of organisation of the 15M movement and the experiences of Dutch radical left activists to inform a better appreciation of the radical potential of a certain variant of noise: pink noise.